PJMHS 2021
DOI: 10.53350/pjmhs2115123241
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Nonalcoholic Fatty Liver Disease In Covid Positive Diabetic Patients: Cross Sectional Study

Abstract: Background: SARS-CoV-2 principally invades the respiratory system. ACE receptor are also abundant throughout the hepatobiliary system and their increased expression on hepatocyte make patients with NAFLD more vulnerable. Aim: To see outcomes of COVID positive diabetic patients suffering from Nonalcoholic fatty liver disease (NAFLD). Study design: Cross Sectional Study. Methodology: 150 diabetic and COVID PCR positive were recruited from COVID ward of Services Hospital in Lahore. Clinical parameters like BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…One included a cross-sectional study [ 36 ] that was identified as fair quality ( Table S4 ). For the included cohort studies ( Supplementary Table S4 ), 12 of those were rated to be of good quality, while 10 as fair, with no studies rated as poor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One included a cross-sectional study [ 36 ] that was identified as fair quality ( Table S4 ). For the included cohort studies ( Supplementary Table S4 ), 12 of those were rated to be of good quality, while 10 as fair, with no studies rated as poor.…”
Section: Resultsmentioning
confidence: 99%
“…Of the total 5286 patients, 1623 had severe COVID-19, with 33.17% (901/2716) of MAFLD patients having severe COVID-19 disease, as opposed to 28.09% (722/2570) of the non-MAFLD patients. The odds ratio was 1.59 for disease patients with and without MAFLD sensitivity analysis after excluding Tignanelli et al [28][29][30]34,36,38,40,43,[45][46][47][48]52].…”
Section: Mafld and Severity Of Covid-19mentioning
confidence: 96%
See 3 more Smart Citations